Coming from Many Trips. Mobility Experiences of Young People from Bolivian Families in Argentina - Hendel, Verónica; Maggi, María Florencia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
In this article we address the territorial mobilities that cross the life trajectories of young people from Bolivian families with whom we work in Greater Buenos Aires and Córdoba (Argentina). Ethnographic work allowed us to identify the category “travel” as that which is used by young people themselves to name and narrate the multiplicity of displacements they have made at various times in their lives and during different time periods. Travel emerges in the analysis as a generational experience linked to mobility and to certain ways of inhabiting various territories. Intergenerational ties are also present and cross what we will call “threshold tip”, “successive trips” and “visiting trips”. The article contributes to the debate on migrations and mobility, recovering the perspective of young people and proposing categories constructed in the light of fieldwork.